The diagnosis of gallbladder agenesis: two cases report - Tang, Li-Ming (Int J Clin Exp Med, 2015)
Congenital absence of the gallbladder is an extremely rare embryological aberration that is frequently mistaken for cholecystolithiasis; the aim of this study is to investigate the diagnostic methods for agenesis of the gallbladder. Two surgically confirmed gallbladder agenesis cases in our hospital and 75 cases of gallbladder agenesis reported in the literature in China were reviewed. It is extremely difficult to make a correct diagnosis of gallbladder agenesis before operation. When suspected, it may be confirmed by ERCP and MRCP. Interoperate, if no gallbladder can be found during laparoscopy, open surgery should be immediately performed Clinician’s understanding of this disease is of great help in avoiding unnecessary surgical exploration and minimizing the risk of complication. Patients with gallbladder agenesis can be classified into two new types, I: Symptomatic, II: Asymptomatic. Type I can be divided into two subtypes: I a with fatal malformations and I b without fatal malformations.